2022
DOI: 10.1503/jpn.210111
|View full text |Cite
|
Sign up to set email alerts
|

Common and specific patterns of functional and structural brain alterations in schizophrenia and bipolar disorder: a multimodal voxel-based meta-analysis

Abstract: Background: Schizophrenia and bipolar disorder have been linked to alterations in the functional activity and grey matter volume of some brain areas, reflected in impaired regional homogeneity and aberrant voxel-based morphometry. However, because of variable findings and methods used across studies, identifying patterns of brain alteration in schizophrenia and bipolar disorder has been difficult. Methods: We conducted a meta-analysis of differences in regional homogeneity and voxel-based morphometry between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 107 publications
0
6
1
4
Order By: Relevance
“…One of the first neuroimaging findings in SZ was the enlargement of ventricles (Johnstone et al 1976). This was followed by magnetic resonance imaging (MRI) studies demonstrating more subtle grey matter volume loss especially in the prefrontal cortex, superior temporal gyrus and cingulate cortex (Qi et al 2022). A meta-analysis of voxel-based morphometry and diffusion tensor imaging studies revealed widespread white matter alterations including decreased fractional anisotropy in fronto-temporal-limbic pathways (Vitolo et al 2017).…”
Section: Impact Of Neurodevelopmental Disturbances On Brain Connectiv...mentioning
confidence: 99%
“…One of the first neuroimaging findings in SZ was the enlargement of ventricles (Johnstone et al 1976). This was followed by magnetic resonance imaging (MRI) studies demonstrating more subtle grey matter volume loss especially in the prefrontal cortex, superior temporal gyrus and cingulate cortex (Qi et al 2022). A meta-analysis of voxel-based morphometry and diffusion tensor imaging studies revealed widespread white matter alterations including decreased fractional anisotropy in fronto-temporal-limbic pathways (Vitolo et al 2017).…”
Section: Impact Of Neurodevelopmental Disturbances On Brain Connectiv...mentioning
confidence: 99%
“…Отобранные мета-анализы использовали различные методы количественного синтеза данных, такие как, оценка вероятности активации [41,52], многоуровневый анализ плотности ядра [20] и различные варианты картирования на основе областей интересов [19,37,51]. При оценке вероятности активации всех областей мозга было обнаружено достоверно значимое изменение вентральной части задней поясной извилины (область СПРР), характерное, преимущественно, для депрессивной фазы БАР [41], в то же время, при детальном изучении вероятности активации структур СПРР, была зафиксирована сниженная активность задней поясной извилины и предклиний в рамках депрессивной фазы [52] и противоречивые данные об изменении ФК структур СПРР при сравнении пациентов с БАР и нейротипичных респондентов.…”
Section: таблunclassified
“…В то же время эутимия характеризовалась компенсаторным повышением ФК внутри СПРР при снижении между АС и постцентральной извилиной [20,51]. При прицельном изучении активности интересующих областей повышение было выявлено в нижней лобной извилине, правой верхней лобной извилине, островковой коре, правом полосатом теле, а снижение характерно для передней поясной коры, височных областей, правого таламуса, предклиний, левой постцентральной извилины [19,37]. Примечания: фМРТфункциональная Магнитно-резонансная томография; БАРбиполярное аффективное расстройство; БАР-Ддепрессивный эпизод биполярного аффективного расстройства; БАР-Мманиакальный эпизод биполярного аффективного расстройства; БАР-Эфаза эутимии/ремиссии биполярного аффективного расстройства; КГконтрольная группа нейротипичных респондентов; CNKI -Chinese National Knowledge Infrastructure; WoS -Web of Science; ФКфункциональная коннективность покоя областей интереса со всем остальным мозгом; ALFFизменения низкочастотных колебаний; ReHoрегиональная гомогенность; ДКдинамическая коннективность; ICAанализ независимых компонент; VMHCанализ коннективности гомотопических областей; ECMэффективная коннективность; AES-SDM картирование на основе областей интересов с учетом размера эффекта с учетом сглаживания; SDM-PSIкартирование на основе областей интересов с применением пермутационных тестов; MKDAмногоуровневый анализ плотности ядра; ALEоценка вероятности активации; АСаффективная нейросеть; СПРРсеть пассивного режима работы мозга; СВЗсеть выявления значимости; ЦИСцентральная исполнительная сеть; СМСсенсомоторная нейросеть; ДСВ/ВСВдорсальная/вентральная нейросеть внимания.…”
Section: таблunclassified
See 1 more Smart Citation
“…The diverse functional roles of the insula may emerge from its heavy connectivity to an extensive network of cortical and subcortical areas (Benarroch, 2019 ; Cauda et al, 2011 ; Cloutman et al, 2012 ; Gasquoine, 2014 ; Ghaziri et al, 2017 ; Gogolla, 2017 ; Taylor et al, 2009 ). Moreover, a large number of clinical neuroimaging studies have identified the insula as a core region affected across many psychiatric and neurological conditions including, but not limited to, autism (Lukito et al, 2020 ; Nomi et al, 2019 ; Uddin & Menon, 2009 ), schizophrenia (Qi et al, 2022 ; Sheffield et al, 2020 ; Xu et al, 2022 ; Zhu et al, 2015 , 2017 , 2018 , 2020 ; Zhuo, Zhu, Qin, et al, 2017 ), depression (Kim & Han, 2021 ; Nord et al, 2021 ; Yu et al, 2020 ; Zhuo, Zhu, Wang, et al, 2017 ), addiction (Ghahremani et al, 2021 ; Perez Diaz et al, 2021 ; Qiu & Wang, 2021 ; Turel et al, 2021 ; Wei et al, 2017 ), anxiety disorders (Chavanne & Robinson, 2021 ; Cui et al, 2020 ; Feurer et al, 2021 ), Parkinson's disease (Carey et al, 2021 ; Pan et al, 2022 ; Tremblay et al, 2020 ), frontotemporal dementia (Gordon et al, 2016 ; Mandelli et al, 2016 ; Panman et al, 2019 ) and Alzheimer's disease (Jones et al, 2019 ; Liu et al, 2018 ; Nunez et al, 2020 ), highlighting its critical involvement in cross‐disorder neuropathological mechanisms. Collectively, these empirical insights from brain structural and functional data have exposed the insula as an integral component of behavior in various non‐disease and disease states, such that this brain structure has gained considerable attention in basic and clinical neuroscience.…”
Section: Introductionmentioning
confidence: 99%